Pengembangan Media Pembelajaran TCG (Trade Card Game) Untuk Meningkatkan Motivasi Belajar Pada Materi Bangun Ruang KelasVIII SMP Negeri I Tinggimoncong - Khaidir, Khaidir; Thamrin Tayeb; Angriani, Andi Dian; Baharuddin (Department of Mathematics Education, 2025)
This study aims to determine (1) the process of developing TCG (Trade Card Game) learning media to increase learning motivation on solid geometry material for eighth-grade students at SMP Negeri 1 Tinggimoncong, and (2) the quality of TCG learning media in terms of validity, practicality, and effectiveness. This research employs the Research and Development (R&D) method with the ADDIE development model consisting of five stages: Analysis, Design, Development, Implementation, and Evaluation. The developed product is a TCG-based learning media for solid geometry material. The subjects for the trial are 31 students from class VIII.4 at SMP Negeri 1 Tinggimoncong. The instruments used include expert validation sheets, observations of teacher and student activities, student learning motivation questionnaires, teacher response questionnaires, and learning outcome tests. The research results show that: (1) The validity of the TCG learning media is in the